Case report: A rapid response to immunotherapy in a thoracic SMARCA4-deficient undifferentiated tumor with respiratory failure - Shi, Liyong; Lin, Lianshun; Ding, Yin; Zeng, Yiming; Chen, Xiaoyang (Frontiers in Oncology, 2022)
Thoracic SMARCA4-deficient undifferentiated tumor (SMARCA4-UT) is an extremely rare and poor-prognosis malignancy, which was noted as a subtype of lung tumors recently. We presented a case of SMARCA4-UT in a 50-year-old male with progressively worsening respiratory failure. The tumor is the first reported to involve pulmonary artery, and 90% of tumor cells expressed programmed cell death ligand 1 (PD-L1). High tumor mutational burden (TMB, 23.93/Mb) and mutations in SMARCA4 were detected. It is the first reported to receive Tislelizumab monotherapy with considerable improvement in clinical condition and no adverse events. As a result of our case, we highlight the importance of recognizing SMARCA4-UT as an individual entity, as well as the efficacy of immune checkpoint inhibitor therapy, particularly in patients with high levels of TMB and PD-L1 expression.